Preparation method of high surface tension NdFeB magnet anticorrosion coating

By modifying the combination of hydrophilic silica with epoxy resin by silane coupling agent, the problem of insufficient surface tension of neodymium iron boron magnet anticorrosion coating is solved, and the preparation of a high-surface tension coating is achieved, ensuring the stability and safety of the bonding process.

CN117165152BActive Publication Date: 2025-03-18ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311063654.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2023-08-23
Publication Date
2025-03-18
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

The surface tension of existing neodymium iron boron magnet anticorrosion coatings is low, resulting in unstable or even degummed during the bonding process, which poses safety hazards.

Method used

By modifying hydrophilic silica with silane coupling agent, combined with epoxy resin and acid catalyst, a high surface tension NdFeB magnet anticorrosion coating was prepared. This method increases the surface tension of the coating by forming chemical bonds in the coating.

Benefits of technology

The high surface tension of the NdFeB magnet coating is achieved, ensuring the stability and safety of the bonding process and extending the service life of the magnet.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of coatings, and aims to provide a method for preparing a high surface tension NdFeB magnet anticorrosion coating. The method comprises: adding epoxysilane and propylene glycol methyl ether to a reactor, stirring and mixing evenly under heating conditions; dissolving an acid catalyst in deionized water to obtain an acid catalyst aqueous solution; adding the acid catalyst aqueous solution to the reactor, stirring and reacting at 30°C to obtain a modified dispersion; adding silicon dioxide to the reactor, stirring at 30°C for 2h, cooling to room temperature, and obtaining a modified hydrophilic silicon dioxide dispersion; adding epoxy resin and slurry to the dispersion, stirring and dispersing for 2h, and obtaining a NdFeB anticorrosion coating. The present invention gives full play to the characteristics of the hydrophilic silicon dioxide surface containing hydrophilic functional groups, and after being modified by a silane coupling agent with an epoxy group, it can undergo a cross-linking reaction with epoxy resin to form a network structure. Not only the surface tension of the coating is effectively improved, but also the anticorrosion performance of the coating can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings and relates to a method for preparing a high surface tension NdFeB magnet anticorrosive coating. Background Art

[0002] NdFeB permanent magnet materials have high remanence and maximum magnetic energy product, as well as good dynamic recovery characteristics and high cost performance. They are widely used in rail transportation, energy-saving and new energy vehicles, permanent magnet motors and other fields. The microstructure of NdFeB magnets is composed of the main phase, the grain boundary Nd-rich phase, the boron-rich phase, etc. Among them, the Nd-rich phase is easily corroded by water vapor and oxygen in the air, causing the magnetic properties to fail. Therefore, it is necessary to form a protective layer on the surface of the magnet to extend its service life. Organic anti-corrosion coating is the current mainstream application technology, among which epoxy materials are the most common.

[0003] In the production process of permanent magnet motors, bonding technology is required to ensure the mechanical reliability of the rotor under high-speed rotation (12000r / min). However, the surface of the epoxy coating contains hydrophobic functional groups and has a low surface tension (generally 28-30mN / m); it is easy to become loose or even debond during bonding, posing a major safety hazard.

[0004] Researchers have conducted research on the surface affinity of coatings / platings on NdFeB magnets. The research results reported so far, such as the Chinese patent document CN 116037431 A, record a method for increasing the surface tension of the coating. Although high surface tension can be obtained under plasma treatment, and the coating maintains ≥50mN / m within 6 months, the surface tension of the coating after plasma treatment will gradually decrease over time, and plasma treatment requires the addition of new process flows. For example, Gao Chu et al. "Improvement of Surface Tension of NdFeB Nickel-Copper-Nickel Plating" (Contemporary Chemical Research, 2021, 12: 167-169); the control method provided in the document can increase the surface tension of nickel-copper-nickel plating, with an initial surface tension of ≥42mN / m and ≥36mN / m after four months of storage, but the report is limited to electroplating systems.

[0005] Therefore, there is a practical need to provide a method for preparing a high surface tension NdFeB magnet anti-corrosion coating, which can achieve high surface tension at the source of coating preparation to prevent the NdFeB magnet from being loose or even debonding during bonding. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high surface tension NdFeB magnet anticorrosive coating.

[0007] To solve the technical problem, the solution of the present invention is:

[0008] Provided is a method for preparing a high surface tension NdFeB magnet anticorrosion coating, comprising the following steps:

[0009] (1) taking a pigment, a filler and an ether solvent in a mass ratio of 1:1:2, mixing them uniformly; and obtaining a slurry after sand grinding;

[0010] (2) adding epoxysilane and propylene glycol methyl ether in a mass ratio of 1-2:200-400 into a reaction kettle; stirring under heating conditions to fully mix to obtain a mixed solution A;

[0011] (3) dissolving the acid catalyst in deionized water to obtain an acid catalyst aqueous solution with a mass percentage of 10 to 20%;

[0012] (4) adding the acid catalyst aqueous solution to the mixed solution A in a mass ratio of 1 to 2:1000 into a reaction kettle and mixing with the mixed solution A; and then stirring and reacting at 30° C. for 20 minutes to obtain a modified dispersion;

[0013] (5) taking silica particles and modified dispersion in a mass ratio of 4-8:100-200, mixing and stirring at 30° C. for 2 h; cooling to room temperature to obtain modified hydrophilic silica dispersion;

[0014] (6) Epoxy resin, slurry and modified hydrophilic silica dispersion are mixed in a mass ratio of 100-200:100-200:100-200, stirred and dispersed for 2 hours to obtain a high surface tension NdFeB magnet anti-corrosion coating.

[0015] As a preferred embodiment of the present invention, in the step (1), the pigment, filler and ether solvent are first stirred and mixed uniformly in a mixing barrel, and then transferred to a sand milling tank and sand milled for 10 hours to obtain a slurry.

[0016] As a preferred embodiment of the present invention, in step (1), the pigment is at least one of iron red, chrome yellow or cobalt blue; the filler is at least one of calcium carbonate, mica or talc; and the ether solvent is propylene glycol methyl ether.

[0017] As a preferred embodiment of the present invention, in step (2), the epoxysilane is one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltriethoxysilane; the heating temperature is controlled to be 30°C and the stirring time is 20 minutes.

[0018] As a preferred embodiment of the present invention, in step (3), the acid catalyst is one or more combinations of acetic acid, formic acid or hydrochloric acid solution.

[0019] As a preferred embodiment of the present invention, in step (5), the silicon dioxide particles are hydrophilic silicon dioxide with a particle size of ≤100 nm.

[0020] As a preferred embodiment of the present invention, in step (6), the epoxy resin is one or a combination of E44 epoxy resin and E51 epoxy resin.

[0021] The present invention further provides a method for using the high surface tension NdFeB anti-corrosion coating prepared by the above method, comprising the following steps:

[0022] (1) mixing the anticorrosive coating and the epoxy curing agent in a mass ratio of 100:6.5-15; stirring evenly to obtain a material for construction;

[0023] (2) Spray the construction material onto the surface of the NdFeB magnet, and solidify it after drying to form a coating; control the spraying amount so that the thickness of the coating is 25 to 35 μm.

[0024] As a preferred embodiment of the present invention, the spraying is performed using dried and cooled compressed air, and the spraying pressure is controlled to be 0.5 MPa.

[0025] As a preferred embodiment of the present invention, the drying treatment refers to sending the sprayed NdFeB magnet into a baking furnace, heating it to 80° C. and keeping it for 30 minutes, and then cooling it naturally.

[0026] Description of the invention principle:

[0027] 1. Hydrophilic silica is added to the coating, which can increase the surface tension of the coating after curing and enhance the anti-corrosion ability. The existing common process is to disperse silica directly into the coating mechanically, but this dispersion method easily causes the agglomeration of silica powder, making it difficult to achieve true nano-level dispersion uniformity.

[0028] 2. In the prior art, the usual application method of hydrophilic silica is to add it to a water-based system to improve the fluidity of water-based coatings and enhance the mechanical properties of coatings. However, in an organic system, hydrophilic silica cannot be well dispersed after being added. The present invention modifies hydrophilic silica with a silane coupling agent, so that hydrophilic silica can be well dispersed in a solvent-based epoxy coating.

[0029] 3. Hydrophilic silica can improve the anti-corrosion performance, weather resistance, strength, hardness, and UV resistance of coatings. In addition, during the film-forming process, nano-silica particles can effectively improve the interfacial bonding tension between polymers and between polymers and fillers, thereby achieving the effect of strengthening and repairing defects, thereby effectively improving the mechanical properties of the coating after film formation. Therefore, hydrophilic silica is widely used in coating preparation technology, but usually only the above-mentioned properties are used.

[0030] In the existing open literature, there is no record of using hydrophilic silica to increase the surface tension of the coating, and in particular, there is no record of using a silane coupling agent to modify silica to subsequently increase the surface tension of the coating.

[0031] 4. The present invention disperses silicon dioxide in epoxy coating by using silane coupling agent. This allows silicon dioxide to form a chemical bond with the interface of epoxy polymer, rather than a simple mixing of the two components. The specific implementation process can be described as follows: Under the action of an acidic catalyst, silane with epoxy groups can be hydrolyzed to generate silanols, which can be combined with inorganic silicon dioxide. At the same time, the epoxy groups in silane can react and combine with organic matter. Therefore, through the silane coupling agent, a "molecular bridge" is built between the interface of inorganic and organic matter, and a high surface tension NdFeB magnet anti-corrosion coating is prepared.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention gives full play to the characteristics of hydrophilic functional groups on the surface of hydrophilic silica, and after being modified by a silane coupling agent with an epoxy group, it can undergo a cross-linking reaction with epoxy resin to form a network structure. It not only effectively increases the surface tension of the coating, but also improves the anti-corrosion performance of the coating.

[0034] 2. After the hydrophilic silica is modified by a silane coupling agent with an epoxy group, it can be applied not only to water-based systems but also to organic solvent systems. It can also be compounded with other organic resins, thus achieving a combination of more preferred solutions. DETAILED DESCRIPTION

[0035] The following specific embodiments illustrate the implementation of the present invention, and those familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The exemplary embodiments can be implemented in various forms and should not be construed as being limited to the examples described herein; on the contrary, these embodiments are provided so that the present invention will be more comprehensive and complete, and the concept of the exemplary embodiments will be fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner.

[0036] Embodiment 1:

[0037] 1. Prepare slurry

[0038] Red iron oxide, calcium carbonate powder and propylene glycol methyl ether were taken in a mass ratio of 1:1:2, and stirred and mixed evenly in a mixing barrel; then the mixture was moved to a sand milling tank and sanded for 10 hours to obtain a slurry.

[0039] 2. Preparation of high surface tension NdFeB magnet anti-corrosion coating

[0040] (1) adding epoxysilane and propylene glycol methyl ether in a mass ratio of 1:400 into a reaction kettle; stirring at 30° C. for 20 min, mixing thoroughly and uniformly to obtain a mixed solution A; the epoxysilane is γ-(2,3-epoxypropoxy)propyltrimethoxysilane;

[0041] (2) dissolving formic acid in deionized water to obtain a 10% by weight formic acid aqueous solution;

[0042] (3) adding hydrochloric acid aqueous solution into the reaction kettle containing mixed solution A at a mass ratio of 1:1000, stirring and reacting at 30° C. for 20 min to obtain a modified dispersion;

[0043] (4) adding hydrophilic silica (particle size ≤ 100 nm) at a mass ratio of 8:100 into the reaction kettle containing the modified dispersion in step (3), stirring at 30° C. for 2 h, and cooling to room temperature to obtain a modified hydrophilic silica dispersion;

[0044] (5) E44 epoxy resin and slurry were added to the modified hydrophilic silica dispersion at a mass ratio of 150:150:150, and the mixture was stirred and dispersed for 2 hours to obtain a high surface tension NdFeB magnet anticorrosion coating.

[0045] 3. Compounding and coating

[0046] (1) The high surface tension NdFeB magnet anticorrosive coating and the phenolic amine epoxy curing agent (T31) were stirred and mixed evenly at a ratio of 100:8;

[0047] (2) Spraying the mixed coating onto the surface of the NdFeB magnet using dried and cooled compressed air at a spraying pressure of 0.5 MPa;

[0048] (3) The sprayed NdFeB magnet is sent to a baking furnace, heated to 80°C and maintained for 30 minutes; after natural cooling, a coating with high surface tension is solidified on the surface of the NdFeB magnet. The spraying amount in the previous step is controlled so that the thickness of the film formed after drying is 25 to 35 μm.

[0049] Embodiment 2:

[0050] 1. Prepare slurry

[0051] Take medium chrome yellow, calcium carbonate, mica powder and propylene glycol methyl ether in a mass ratio of 1:0.5:0.5:2, stir and mix them evenly in a mixing barrel; then move them to a sand mill and sand grind them for 10 hours to obtain a slurry.

[0052] 2. Preparation of high surface tension NdFeB magnet anti-corrosion coating

[0053] (1) adding epoxysilane and propylene glycol methyl ether in a mass ratio of 2:200 into a reaction kettle; stirring at 30° C. for 20 minutes and mixing thoroughly to obtain a mixed solution A; the epoxysilane is γ-(2,3-epoxypropoxy)propyltriethoxysilane;

[0054] (2) dissolving hydrochloric acid in deionized water to obtain a 20% by weight hydrochloric acid aqueous solution;

[0055] (3) adding a formic acid aqueous solution into the reaction kettle containing the mixed solution A at a mass ratio of 2:1000, stirring and reacting at 30° C. for 20 min to obtain a modified dispersion;

[0056] (4) adding hydrophilic silica (particle size ≤ 100 nm) at a mass ratio of 4:200 into the reaction kettle containing the modified dispersion in step (3), stirring at 30° C. for 2 h, and cooling to room temperature to obtain a modified hydrophilic silica dispersion;

[0057] (5) E51 epoxy resin and slurry were added to the modified hydrophilic silica dispersion at a mass ratio of 100:100:100, and the mixture was stirred and dispersed for 2 hours to obtain a high surface tension NdFeB magnet anticorrosion coating.

[0058] 3. Compounding and coating

[0059] (1) The high surface tension NdFeB magnet anticorrosive coating and the phenolic amine epoxy curing agent (T31) were stirred and mixed evenly at a ratio of 100:6.5;

[0060] (2) Spraying the mixed coating onto the surface of the NdFeB magnet using dried and cooled compressed air at a spraying pressure of 0.5 MPa;

[0061] (3) The sprayed NdFeB magnet is sent to a baking furnace, heated to 80°C and maintained for 30 minutes; after natural cooling, a coating with high surface tension is solidified on the surface of the NdFeB magnet. The spraying amount in the previous step is controlled so that the thickness of the film formed after drying is 25 to 35 μm.

[0062] Embodiment 3:

[0063] 1. Prepare slurry

[0064] Cobalt blue, red iron oxide, calcium carbonate, talcum powder and propylene glycol methyl ether were taken in a mass ratio of 0.5:0.5:0.5:0.5:2, and stirred and mixed evenly in a mixing barrel; then moved to a sand mill tank and sand milled for 10 hours to obtain a slurry.

[0065] 2. Preparation of high surface tension NdFeB magnet anti-corrosion coating

[0066] (1) adding epoxysilane and propylene glycol methyl ether in a mass ratio of 1.5:225 into a reaction kettle; stirring at 30° C. for 20 min, mixing thoroughly and uniformly to obtain a mixed solution A; the epoxysilane is γ-(2,3-epoxypropoxy)propyltriethoxysilane;

[0067] (2) mixing hydrochloric acid and acetic acid in a mass ratio of 1:2 and dissolving them in deionized water to obtain an acid catalyst aqueous solution with a mass percentage of 15%;

[0068] (3) adding the acid catalyst aqueous solution into the reaction kettle containing the mixed solution A at a mass ratio of 1.5:1000, stirring and reacting at 30° C. for 20 minutes to obtain a modified dispersion;

[0069] (4) adding hydrophilic silica (particle size ≤ 100 nm) at a mass ratio of 6:150 into the reaction kettle containing the modified dispersion in step (3), stirring at 30° C. for 2 h, and cooling to room temperature to obtain a modified hydrophilic silica dispersion;

[0070] (5) E51 epoxy resin, E44 epoxy resin and slurry were added to the modified hydrophilic silica dispersion at a mass ratio of 100:100:200:200, and the mixture was stirred and dispersed for 2 hours to obtain a high surface tension NdFeB magnet anti-corrosion coating.

[0071] 3. Compounding and coating

[0072] (1) Stir and mix the high surface tension NdFeB magnet anticorrosive coating with a phenolic amine epoxy curing agent (T31) at a ratio of 100:15;

[0073] (2) Spraying the mixed coating onto the surface of the NdFeB magnet using dried and cooled compressed air at a spraying pressure of 0.5 MPa;

[0074] (3) The sprayed NdFeB magnet is sent to a baking furnace, heated to 80°C and maintained for 30 minutes; after natural cooling, a coating with high surface tension is solidified on the surface of the NdFeB magnet. The spraying amount in the previous step is controlled so that the thickness of the film formed after drying is 25 to 35 μm.

[0075] Comparative Example 1

[0076] Take E44 epoxy resin without adding high surface tension slurry, stir and mix with phenolic amine epoxy curing agent (T31) at a ratio of 100:8, and then spray directly onto the same substrate surface according to the method of Example 1.

[0077] Comparative Example 2

[0078] Take E51 epoxy resin without adding high surface tension slurry, stir and mix with phenolic amine epoxy curing agent (T31) at a ratio of 100:6.5, and then spray directly onto the same substrate surface according to the method of Example 1.

[0079] Comparative Example 3

[0080] 100 parts by mass of E44 epoxy resin and 100 parts by mass of E51 epoxy resin without adding high surface tension slurry were mixed with phenolic amine epoxy curing agent (T31) at a ratio of 100:15, and then directly sprayed onto the same substrate surface according to the method of Example 1.

[0081] Comparative Example 4

[0082] According to patent CN202310062584, the dyne value of the untreated NdFeB surface is generally 28-30mN / m.

[0083] Comparative Example 5

[0084] According to an article in the journal Contemporary Chemical Research on the improvement of surface tension of NdFeB nickel-copper-nickel coatings, it is known that the initial surface dyne value of NdFeB coated with nickel-copper-nickel coating is ≥42mN / m, and the surface dyne value after storage for 4 months is ≥36mN / m.

[0085] The surface dyne value of the magnet surface coating in each embodiment and comparative example was tested by the following method:

[0086] Apply the test ink (surface tension test range 28~72mN / m) produced by Plasmatreat of Germany to the coating surface. If the liquid wets the surface (i.e. the liquid spreads continuously on the surface), the surface tension of the tested coating is higher than the nominal surface tension of the test ink. Continue to select a higher grade of test ink and repeat the above process until the liquid no longer wets the surface (i.e. the liquid shrinks on the surface). The nominal surface tension on the package of the last test ink that wets the surface and remains unshrinked for 2S is the surface tension of the tested coating. The test results are shown in Table 1.

[0087] Table 1

[0088] Paint samples Surface dyne value (mN / m) Example 1 54-56 Example 2 46-48 Example 3 50-52 Comparative Example 1 30-32 Comparative Example 2 30-32 Comparative Example 3 30-32 Comparative Example 4 28-30 Comparative Example 5 36

[0089] It can be seen from the test data in Table 1 that the present invention uses modified hydrophilic silica to treat the epoxy resin film-forming material. The NdFeB magnet anticorrosive coating product finally obtained by the present invention has a coating surface tension of 46 to 52 mN / m after curing, which can meet the requirements of the viscose surface tension (usually 36 mN / m or more).

[0090] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a high surface tension NdFeB magnet anticorrosion coating, characterized in that: The following steps are involved: (1) Pigment, filler and ether solvent are mixed uniformly in a mass ratio of 1:1:2; and slurry is obtained after sand grinding; Specifically, the pigment, filler and ether solvent are first stirred and mixed in a mixing barrel, and then moved to a sand milling tank and sand milled for 10 hours to obtain a slurry; (2) adding epoxysilane and propylene glycol methyl ether in a mass ratio of 1-2:200-400 to a reaction kettle; stirring under heating conditions to fully mix to obtain a mixed solution A; the epoxysilane is one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(2,3-epoxypropoxy)propyltriethoxysilane; controlling the heating temperature to 30°C and the stirring time to 20 min; (3) dissolving an acid catalyst in deionized water to obtain an acid catalyst aqueous solution with a mass percentage of 10-20%; the acid catalyst is one or more combinations of acetic acid, formic acid or hydrochloric acid solution; (4) adding the acid catalyst aqueous solution to the mixed solution A into the reaction kettle at a mass ratio of 1 to 2:1000; then stirring and reacting at 30°C for 20 minutes to obtain a modified dispersion; (5) taking silica particles and modified dispersion in a mass ratio of 4-8:100-200, mixing and stirring at 30°C for 2 hours; cooling to room temperature to obtain a modified hydrophilic silica dispersion; the silica particles are hydrophilic silica with a particle size of ≤100 nm; (6) Epoxy resin, slurry and modified hydrophilic silica dispersion are taken in a mass ratio of 100-200:100-200:100-200, mixed and stirred for 2 hours to obtain a high surface tension NdFeB magnet anti-corrosion coating.

2. The method according to claim 1, characterized in that In the step (1), the pigment is at least one of iron oxide red, chrome yellow or cobalt blue; the filler is at least one of calcium carbonate, mica or talc; and the ether solvent is propylene glycol methyl ether.

3. The method according to claim 1, characterized in that In the step (6), the epoxy resin is one or a combination of E44 epoxy resin and E51 epoxy resin.

4. A method for using the high surface tension NdFeB anticorrosive coating prepared by the method of claim 1, characterized in that: The following steps are involved: (1) Mix the anticorrosive coating and the epoxy curing agent in a mass ratio of 100:6.5-15; stir evenly to obtain a material for construction; (2) Use dried and cooled compressed air to spray the construction materials on the surface of the NdFeB magnet, and control the spraying pressure to 0.5MPa; after drying, solidify to form a coating; control the spraying amount so that the coating thickness is 25~35μm.

5. The method according to claim 4, characterized in that The drying treatment refers to sending the sprayed NdFeB magnet into a baking furnace, heating it to 80° C. and keeping it for 30 minutes, and then cooling it naturally.

Citation Information

Patent Citations

  • Method for improving surface tension of nano coating

    CN116037431A

  • A method for increasing the surface tension of nano coatings

    CN116037431B

  • Preparation method of neodymium-iron-boron magnet

    CN110676043A

  • Liquid crystal epoxy resin-mesoporous silica composite material, preparation method and application

    CN113563693A

  • Golf ball including delusterant and method for producing the same

    US20220401796A1